Caracterización de los microbiomas de suelos en plantaciones cafetaleras comerciales del Ecuador - Bajaña Santana, Henrry Gaudencio (2023)
In Ecuador it is estimated that there are around 230 000 planted of coffee, this wide distribution is present because Ecuador is one of the 14 countries, out of around 70, that grows both commercial coffee species. Therefore, in addition to being a highly specialized crop, all components of the production system must be managed between themselves and the soil. For this, the microbiota plays an important role in defending against diseases, promoting plant growth, as well as changing vegetation. In the case of coffee, the information present in microbiome studies is, in many cases, insufficient. In this concept we seek to characterize the soil microbiomes in commercial coffee plantations in Ecuador. For this purpose, a bibliographic review was carried out on scientific evidence related to microbiomes in coffee cultivation worldwide and in the country. Through paraphrasing and selection of quotes, quite controversial and contradictory results will be found. According to the results, it is indicated that in Ecuador there is little knowledge, or in many cases incipient, the study of soil microbiomes. This is due to a certain extent to the training of researchers in the area; the study carried out shows that a lot of development is needed in soil science at the local level. The review carried out details with difficulty the scarcity of relevant academic works that indicate in detail the different conformations of soil microbiomes and their importance in agricultural production. In many cases, these studies are even less precise due to the difficulties encountered when identifying the microbial agents present in the samples studied. It is also evident that in the sectors where microbiome studies were carried out, considerable genetic variability was found for fungi, bacteria, and other microorganisms. In other aspects, there are groups based on the preference of organisms that are better adapted to certain particularities of the environment in which they live, in addition, there are isolated populations without identification.